Solution-phase synthesis of the macrocyclic core of teixobactin - Dhara, Santu; Gunjal, Vidya B.; Handore, Kishor L.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
Towards the total chemical synthesis of the exceptionally potent antibiotic teixobactin, we synthesized the macrocyclic core of a natural product by using a solution-phase approach. The gramscale synthesis of L-allo-enduracididine and Shiina macrolactonization are highlights of the present disclosure.

Synthetic studies towards Pseudoxylallemycin B, an antibiotic active against gram-negative bacteria: total synthesis of 3-epi-Pseudoxylallemycin B - Gunjal, Vidya B. (Tetrahedron Letters, 2018)
In an attempt towards the total synthesis of Pseudoxylallemycin B, a homo dimeric, N-methylated macrocyclic tetrapeptidic natural product, synthesis of its epimer at position 3 (d-Tyr instead of l-Tyr) is described here. During the course of synthesis we came across a striking yet unusual observation of complete epimerization which led to the formation of 3-epi-Pseudoxylallemycin B.
Keywords: Cyclic tetrapeptides; Epimerization; Gram-negative bacteria; Macrolactamization; Propyl phosphonic anhydride (T3P)